Modelling and simulation of an analytical approach to handle real-time traffic in VoIP network. (2018) - Kaushal, Sakshi; Kumar, Harish; Singh, Sarbjeet; Aggarwal, Shubhani; Kaur, Jasleen; Vaidyanathan, Sundarapandian
In recent years, internet protocol (IP) has become a good choice over public switched telephone network (PSTN). VoIP implementation uses hard IP phones, soft IP phones and uses Softswitch for call signalling. The Erlang B model is used to determine number of trunks in circuit switched network and found traffic intensity and grade of service (GoS). This paper utilises an extension of Erlang B model for traffic engineering VoIP, i.e., extended Erlang B model. The main purpose for extended Erlang B is that it has better efficiency to handle the percentage of blocked calls by choosing a threshold value (∝). We propose a new measurement scheme based on extended Erlang B model using FreeSWITCH and simulated and analysed VoIP traffic. We compare our version with the original definition of EB model and present further results from simulations. The proposed scheme is also analysed for other QoS parameters, i.e., jitter, end to end delay and MOS.